Competitive balance trends in elite table tennis: the Olympic Games and World Championships 1988-2016 - Zheng, J.; Oh, T.; Kim, S.; Dickson, G.; de Bosscher, V. (Journal of Sports Sciences, 2018)
Competitive balance is important because it enhances outcome uncertainty and therefore it promotes spectator interest, and encourages government investment in a sport. This article analyses the distribution of gold medals, medals, medal points and top eight points amongst nations in table tennis from 1988 to 2016 at the Olympic Games and the World Championships respectively. A normalised version of the Herfindahl-Hirschman Index and a coefficient of variation are calculated for each nation`s share of these performance indicators. The key findings are that China dominates both events, with successful female players being more dominant than their male counterparts. The competitive balance for gold medals has declined, whilst there is a trend towards improved competitive balance for top eight points for women, suggesting that more teams are featuring in the top eight (but not necessarily the top three) placings. This research has implications for the development of table tennis competitions. Compared to other racket sports, the issue of competitive imbalance in table tennis is particularly thorny, which threatens the long-term development of this sport. Accordingly, some measures are recommended for the International Olympic Committee and the International Table Tennis Federation to propel a more balanced development of international table tennis.